Perbandingan Pemberian Sanksi Pencemaran Nama Baik di Media Sosial antara Indonesia dan Arab Saudi - Anisa Mufida (ADALAH, 2020)
AbstractArticle 27 paragraph (3) and Article 45 Paragraph (1) of the Law on Information and Electronic Transactions Number 11 of 2008 regulates criminal prosecution of defamation in the Republic of Indonesia, whereas in Saudi Arabia stipulates it in article 3 which states a sentence of imprisonment for a term no more than one year and a fine not exceeding five hundred thousand riyals (2 billion), or one of these two sentences. Judges in Indonesia usually impose conditional penalties for defendants of defamation by considering press freedom and opinion, the rights of consumers and patients, and the right to obtain information before convicting convictions, in contrast to Saudi Arabia which provides final decisions in accordance with applicable law.Keywords: Defamation, ITE, Judges.AbstrakPasal 27 ayat (3) dan Pasal 45 Ayat (1) UU ITE mengatur tentang pemidanaan pencemaran nama baik di negara Republik Indonesia, sedangkan di Arab Saudi menetapkannya dalam pasal 3 yang menyatakan Hukuman penjara untuk jangka waktu tidak lebih dari satu tahun dan denda tidak melebihi lima ratus ribu riyal (2 milyar), atau salah satu dari dua hukuman ini. Hakim di Indonesia biasanya menjatuhkan  pidana  bersyarat  bagi  terdakwa pencemaran nama baik dengan  mempertimbangkan kemerdekaan pers dan berpendapat, hak konsumen dan pasien, serta hak untuk mendapatkan informasi sebelum menjatuhkan putusan pemidanaan, berbeda dengan Arab Saudi yang memberikan putusan akhir sesuai dengan undang-undang yang berlaku.Kata Kunci : Pencemaran Nama Baik, ITE, Hakim.